Local-carbon leadership: Harnessing policy studies to analyse local mayors and renewable energy transitions in three Japanese cities - Takao, Yasuo (Elsevier, 2020)
This paper examines the roles of local governments that are in the early stages of a transformation from centralised to decentralised energy, while drawing on the lessons learned from the experience of three municipalities in Japan. The author asks what drives the transition to renewable energy at the local level. In the past, the studies of energy transitions have made very little use of the theories of policy studies. Therefore, this research harnesses the process-oriented theories of policy studies for examining the dynamic and complex process of on-going decision making in these transitions. This study found that the effective transitions to renewable energy in Japanese towns result largely from conflict-free policy coordination, which the author argues was produced by forward-looking local mayors.